PERBANDINGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SISTEM BAHAN BAKAR YANG MENGGUNAKAN STRATEGI PEMBELAJARAN KREATIF PRODUKTIF DENGAN STRATEGI PEMBELAJARAN GENERATIF DI SMKN 1 INDERALAYA UTARA - Hendri Irawansyah; Ali Fikri Asri; Ahmad Burhan (Jurnal Pendidikan Teknik Mesin, 2015)
The study was titled: "a comparison of the results of student learning on subjects the fuel system that uses a Creative Productive Learning Strategy With Generative Learning Strategy In SMK N 1 Inderalaya North". The purpose of this research is to know the results of the comparison of student learning on subjects the fuel system that uses a creative productive learning strategy with generative learning strategy in SMK N 1 Inderalaya North. This research method is the comparison. Research data is collected using the techniques of observation and tests. The population in this research is the whole grade XI 1 North Inderalaya year 2014-2015 lessons totalling 60 persons, whereas samples taken the same amount of the population. Based on the research results obtained revealed that the experimental group of students learning activities I use creative learning strategies of higher than group II experiments using generative learning strategies or mathematically 81,63 > 79,84. While the results of student learning on subjects the fuel system that uses a creative productive learning strategy is greater than using generative learning strategy in SMK N 1 Inderalaya North or 78,83 > 74,83.